'Eating your own dog food': applying course concepts in your teaching. (1st January 2012) - Bregman, Robert L.
The phrase 'eating your own dog food', which relates to the internal use of products for sale to customers, is common in the software industry. The phrase and the general approach provide an interesting way to promote the use of course concepts to students. In short, the 'eating your own dog food' approach requires an instructor to use course concepts in the design and management of a class, and convey those linkages to students during the class. This article introduces the approach in general and describes how it was used to improve an online graduate core class in operations management.